Tl1MBUH KEMBANG ANAK USIA TAMAN KANAK-KANAK (TK) DAN GA YA BELAJAR YANG DIMILIKINYA - Nelva Rolina (Dinamika Pendidikan, 2009)
Kindergarten children who have 4-6 ages old are include in early childhood  who have 0-8 ages old. Early childhood is the golden age which is observed.  Every life span development in early childhood should be our focus, because every step has the special unique character. Some people said that if child under 4 years old intellectual development  is not maximize, .\'0 it can he stop unti! 7 years old. The stimulation which is give as same as with individual child character: one oj them is learning style of child. Every child has different learning  style. They are visual learning style, auditory learning style, and kinesthetic learning style, Stimulation with unique rhararter and  learning style are  good focus  in  growth and  development of kindergarten children.   Key Words: Growth and Development, Kindergarten Children, Learning Style.